Associations between low HDL, sex and cardiovascular risk markers are substantially different in sub-Saharan Africa and the UK: analysis of four population studies. Issue 5 (20th May 2021) - Greiner, Rosamund; Nyrienda, Moffat; Rodgers, Lauren; Asiki, Gershim; Banda, Louis; Shields, Beverly; Hattersley, Andrew; Crampin, Amelia; Newton, Robert; Jones, Angus
Abstract : Introduction: Low high-density lipoprotein (HDL) is widely used as a marker of cardiovascular disease risk, although this relationship is not causal and is likely mediated through associations with other risk factors. Low HDL is extremely common in sub-Saharan African populations, and this has often been interpreted to indicate that these populations will have increased cardiovascular risk. We aimed to determine whether the association between HDL and other cardiovascular risk factors differed between populations in sub-Saharan Africa and the UK. Methods: We compared data from adults living in Uganda and Malawi (n=26 216) and in the UK (n=8747). We examined unadjusted and adjusted levels of HDL and applied the WHO recommended cut-offs for prevalence estimates. We used spline and linear regression to assess the relationship between HDL and other cardiovascular risk factors. Results: HDL was substantially lower in the African than in the European studies (geometric mean 0.9–1.2 mmol/L vs 1.3–1.8 mmol/L), with African prevalence of low HDL as high as 77%. Total cholesterol was also substantially lower (geometric mean 3.3–3.9 mmol/L vs 4.6–5.4 mmol/L). In comparison with European studies the relationship between HDL and adiposity (body mass index, waist to hip ratio) was greatly attenuated in African studies and the relationship with non-HDL cholesterol reversed: in African studies low HDL was associated with lower non-HDL cholesterol. The association between sex and HDL was also different; using the WHO sex-specific definitions, low HDL was substantially more common among women (69%–77%) than men (41%–59%) in Uganda/Malawi. Conclusion: The relationship between HDL and sex, adiposity and non-HDL cholesterol in sub-Saharan Africa is different from European populations. In sub-Saharan Africans low HDL is a marker of low overall cholesterol and sex differences are markedly attenuated. Therefore low HDL in isolation is unlikely to indicate raised cardiovascular risk and the WHO sex-based cut-offs are inappropriate.